PENGARUH TERPAAN MEDIA SOSIAL AKUN INSTAGRAM @ANYAGERALDINE TERHADAP KECENDERUNGAN GAYA HIDUP HEDONIS REMAJA DI KALANGAN FOLLOWERSNYA(Survei Terhadap Followers Akun Instagram @anyageraldine) - Karlina Octaviani, - (2021)
The background in this study explains the influence of social media exposure on the @Anyageraldine Instagram account which aims to determine whether or not there is an influence of social media exposure on the @Anyageraldine Instagram account on the tendency of adolescent hedonic lifestyles among followers by using the S-O-R theory as the basis. This study uses a quantitative research method with an explanatory approach. This research was conducted by sending questionnaires to followers of the @Anyageraldine Instagram account online. Respondents in this study were 100 people who followed the @Anyageraldine Instagram account by using the Taro Yamane formula and the categories that had been determined based on purposive sampling. Based on the results of calculations carried out by the author, the t count is 7,787. From the results of the correlation between variables X (Social Media Exposure @Anyageraldine Instagram Account) with variable Y (Tendency of Adolescent Hedonic Lifestyle), t count (7,865) > t table (1,984) then H0 is rejected and H1 is accepted (magnitude of influence). Determination of significant conclusions by comparing t count with t table, namely: Determination of the level of significance, from the t table the value is determined at the 10% significance level and dfl = n-2, namely 100-2 = 98. Thus the t table value is 1984. Based on the coefficient of determination table shows that R (square) is 0.387. Thus, it can be concluded that there is an influence of social media exposure on the @Anyageraldine Instagram account on the tendency of adolescent hedonic lifestyles by 38.7%.